The Effectiveness of the PjBL Model Assisted by Cloud on Students' Critical Thinking Skills and Environmental Concern Attitudes Regarding Environmental Pollution Topics - Arlistia, Rita; Ratnasari, Jujun; Juanita, Rieska; Windyariani, Sistiana (BIOEDUKASI, 2024)
The 21st century is recognized as the age of knowledge, marked by technological advancements, where students are expected to possess strong critical thinking skills. However, in the realm of science education, students' attitudes towards critical thinking remain relatively low. This is primarily due to the passive reception of information, with students merely memorizing it for examinations or tests. Thus, there is a pressing need for solutions to address these challenges. This research aims to determine the effectiveness of the Cloud-assisted PjBL model on students' critical thinking skills on the topic of Environmental Pollution. The method used was a quasi-experimental. The research instruments were a test for critical thinking skills, a questionnaire for environmental care attitudes, and for the Cloud-assisted PjBL learning response questionnaire. The outcomes indicated that the N-Gain data for the experimental class yielded a value of 0.75, indicating a high category, while the control class obtained a value of 0.49, indicating a medium category. The average result for environmental care attitudes among students in the experimental and control class is good. The conclusion in this research is that the Cloud-assisted PjBL model is effective on students' critical thinking skills and can improve students' environmental care attitudes.